Novel quinoline derivatives as green corrosion inhibitors for mild steel in acidic medium: Electrochemical, SEM, AFM, and XPS studies - Singh P.; Srivastava V.; Quraishi M.A. (My University, 2025)
The corrosion mitigation effect of quinoline derivatives such as 2-amino-7-hydroxy-4-phenyl-1,4-dihydroquinoline-3-carbonitrile (Q-1), 2-amino-7-hydroxy-4-(p-tolyl)-1,4 dihydroquinoline-3-carbonitrile (Q-2), 2-amino-7-hydroxy-4-(4-methoxyphenyl)-1,4 dihydroquinoline-3 carbonitrile (Q-3), 2-amino-4-(4-(dimethylamino)phenyl)-7-hydroxy-1,4-dihydroquinoline-3-carbonitrile (Q-4) were analyzed using weight loss, electrochemical impedance spectroscopy (EIS) and potentiodynamic polarizations. Among all the investigated inhibitors, Q-4 showed the maximum inhibition efficiency of 98.09% at 150 mg/l. The electrochemical impedance spectroscopy (EIS) measurements revealed that corrosion inhibition takes place due to the adsorption of inhibitor molecules on the metal surface. The potentiodynamic polarization measurements show that Q-1, Q-2, Q-3 act as a mixed-type inhibitor while Q-4 acts as a cathodic inhibitor. The adsorption of quinolines on mild steel surface obeyed the Langmuir adsorption isotherm. The surface analysis techniques (SEM/AFM/XPS) further corroborate that the corrosion inhibition occurs due to the adsorption of the inhibitor molecules at the metal/solution interface. © 2015 Elsevier B.V.